Unpacking English Writing Anxiety in Indonesian EFL Learners: A Mixed-Methods Study of Cognitive Strain, Gender, and Academic Level - Iis Sujarwati; Ira Maisarah; Dwi Bayu Saputra; Tiarsa Julmukya (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
Background: Writing anxiety became a tenacious factor hindering EFL students’ proficiency, specifically at the higher education level. In the Indonesian context, undergraduate and graduate students face a high demand to complete their studies. Writing a thesis is one of the requirements for graduation at the undergraduate level. Meanwhile, the graduate students must write a research article for publication as another requirement. Those things become a contributing factor to students feeling anxious in writing. A bulk of studies investigated the writing anxiety around the world. However, a few studies examine how gender and academic level differentiate the English language education study program students’ writing anxiety in Indonesia. This present study uncovers: 1) types and levels of writing anxiety among the groups, 2) variation of writing anxiety based on gender and academic levels, and 3) reasons affecting writing anxiety. Methodology: A sequential explanatory mixed-methods design was deployed in this study. The sample was 112 students, including 58 undergraduates and 54 graduates, of the English language education study program at a state university in Bengkulu, Indonesia. Two different data collection methods were implemented: an online survey and an on-site focus-group discussion (FGD). The second language writing anxiety inventory (SLWAI) and the second language writing reason inventory (SLWARI) were derived into fifty-eight items of a questionnaire utilized to obtain quantitative data. Meanwhile, the qualitative data were assembled using four main leading questions to probe students’ thoughts in identifying the factors contributing to anxiety. Quantitative data analysis was preceded by applying SPSS23, including descriptive and inferential statistical analyses. The qualitative data were analyzed through a directed qualitative content analysis (DQCA). Validity and reliability of data were ensured using methodological triangulation. Findings: Statistical analysis revealed that the majority of students, 92%, were at a moderate level of writing anxiety. Besides, cognitive anxiety became the first order of anxiety type experienced by the students. Moreover, the statistical findings presented that there is no significant difference in anxiety based on gender and academic level ( < 0.1). The qualitative analysis elucidated four patterns as contributing factors to the students’ writing anxiety, such as: time constraints, lack of ideas and knowledge, teachers’ teaching methods, and coursebook complexity. Conclusion: Both quantitative and qualitative analyses discovered that cognitive-affective aspects are more challenging for Indonesian students than demographic ones. Moreover, the personal challenges and instructional methods became noteworthy issues that contribute a lot to the emergence of anxiety when writing. Writing teachers need to design engaging and supportive learning environments in their instructional activities, for instance, by adapting a process-oriented writing approach and affording constructive feedback on students’ papers. These efforts can reduce students’ cognitive loads, thereby enhancing their self-efficacy in writing. Originality: The symptom-based SLWAI and the cause-based SLWARI are integrated simultaneously to disclose the writing anxiety experienced by undergraduate and graduate students in the Indonesian context. Additionally, this study implements a mixed-method approach to obtain plentiful, comprehensive data. Accordingly, a more vivid understanding of students’ anxiety in writing can be attained.